Increase in Fracture Risk Following Unintentional Weight Loss in Postmenopausal Women: The Global Longitudinal Study of Osteoporosis in Women. (July 2016) - Compston, Juliet E; Wyman, Allison; FitzGerald, Gordon; Adachi, Jonathan D; Chapurlat, Roland D; Cooper, Cyrus; Díez‐Pérez, Adolfo; Gehlbach, Stephen H; Greenspan, Susan L; Hooven, Frederick H; LaCroix, Andrea Z; March, Lyn; et al.
ABSTRACT: Increased fracture risk has been associated with weight loss in postmenopausal women, but the time course over which this occurs has not been established. The aim of this study was to examine the effects of unintentional weight loss of ≥10 lb (4.5 kg) in postmenopausal women on fracture risk at multiple sites up to 5 years after weight loss. Using data from the Global Longitudinal Study of Osteoporosis in Women (GLOW), we analyzed the relationships between self‐reported unintentional weight loss of ≥10 lb at baseline, year 2, or year 3 and incident clinical fracture in the years after weight loss. Complete data were available in 40, 179 women (mean age ± SD 68 ± 8.3 years). Five‐year cumulative fracture rate was estimated using the Kaplan‐Meier method, and adjusted hazard ratios for weight loss as a time‐varying covariate were calculated from Cox multiple regression models. Unintentional weight loss at baseline was associated with a significantly increased risk of fracture of the clavicle, wrist, spine, rib, hip, and pelvis for up to 5 years after weight loss. Adjusted hazard ratios showed a significant association between unintentional weight loss and fracture of the hip, spine, and clavicle within 1 year of weight loss, and these associations were still present at 5 years. These findings demonstrate increased fracture risk at several sites after unintentional weight loss in postmenopausal women. This increase is found as early as 1 year after weight loss, emphasizing the need for prompt fracture risk assessment and appropriate management to reduce fracture risk in this population. © 2016 American Society for Bone and Mineral Research.